Strategy for Increasing Banking Profitability Listed in Indonesia Stock Exchange - ., Basrowi; Ichwan, Afiful; Rohmah, Rifka Nazilatur; Utami, Pertiwi (International Journal of Economics, Business and Management Studies, 2019)
Every company in running a business aims to maximize profits to improve the welfare of its owners or shareholders. Decisions in the management of the company are an important aspect in obtaining maximum profits. This study aims to determine the effect of company size, asset structure, and debt to total assets ratio (DAR) to profitability. The exchange financial institutions listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period. This type of research is quantitative. The unit of analysis in this study is the issuer of the financial sector with the banking sub sector consisting of 38 banks listed on the Indonesia Stock Exchange. The research methodology used is a statistical analysis method through multiple linear regression and classical assumption tests. Testing the hypothesis by looking at the calculated F value and the calculated t value in the regression test. The results of this study indicate that variable firm size, asset structure, and debt to total assets ratio (DAR) partially or simultaneously have a significant effect on the profitability of stock exchange sector issuers found in the index of the Indonesia Stock Exchange.